2015
DOI: 10.1007/s10709-015-9837-2
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Fusarium wilt race 3 resistance in Upland cotton (Gossypium hirsutum L.)

Abstract: Fusarium wilt [Fusarium oxysporum f.sp. vasinfectum (FOV) Atk. Sny & Hans] represents a serious threat to cotton (Gossypium spp.) production. For the last few decades, the FOV pathogen has become a significant problem in Uzbekistan causing severe wilt disease and yield losses of G. hirsutum L. cultivars. We present the first genetic analyses of FOV race 3 resistance on Uzbek Cotton Germplasm with a series of field and greenhouse artificial inoculation-evaluations and inheritance studies. The field experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Very limited information is available on RNAi directed studies in understanding the resistance of Fusarium oxysporum (FOV) wilting pathogen that has been a serious threat to cotton production across the world ( Abdullaev et al, 2015 ). With the target to develop novel RNAi-based cotton cultivars against FOV, Shapulatov et al (2015) recently characterized a “top-layer” of small RNA/miRNA profile in FOV race 3 infected versus uninfected cotton seedlings of resistant and susceptible cotton genotypes.…”
Section: Rnai For Biotic Stress Studiesmentioning
confidence: 99%
“…Very limited information is available on RNAi directed studies in understanding the resistance of Fusarium oxysporum (FOV) wilting pathogen that has been a serious threat to cotton production across the world ( Abdullaev et al, 2015 ). With the target to develop novel RNAi-based cotton cultivars against FOV, Shapulatov et al (2015) recently characterized a “top-layer” of small RNA/miRNA profile in FOV race 3 infected versus uninfected cotton seedlings of resistant and susceptible cotton genotypes.…”
Section: Rnai For Biotic Stress Studiesmentioning
confidence: 99%
“…W. C. Snyder and H. N. Hansen, FOV] (Cianchetta & Davis, 2015). Fusarium wilt is one of the most destructive diseases of cotton in the United States and other cotton‐growing countries including Brazil, China, India, Egypt, Uzbekistan, and Australia (Abdullaev et al., 2015; Crutcher et al., 2016; Zhang et al., 2015). Fusarium wilt of cotton was first reported in the southern United States in 1892 (Atkinson, 1892).…”
Section: Introductionmentioning
confidence: 99%
“…Research has also explored FOV race 3 resistances in Uzbek cotton germplasm, and genetic analyses indicated that FOV resistance is primarily influenced by a recessive single-gene action under high inoculum levels or disease pressure [77]. These complexities were evident in differing segregation distributions of susceptible and resistant phenotypes among Uzbek populations.…”
Section: The Complexities Of Fusarium: Host Interactions and Disease ...mentioning
confidence: 99%